Active Reward Processing during Human Sleep: Insights from Sleep-Related Eating Disorder - Perogamvros, Lampros; Hasler, Roland; Baud, Patrick; Cloninger, Claude R.; Schwartz, Sophie; Perrig, Stephen (Frontiers in Neurology, 2012)
In this paper, we present two carefully documented cases of patients with sleep-related eating disorder (SRED), a parasomnia which is characterized by involuntary compulsive eating during the night and whose pathophysiology is not known. Using video-polysomnography and psychometric examination, we found that both patients present elevated novelty seeking and increased reward sensitivity on reward-related questionnaires. In light of new evidence on the mesolimbic dopaminergic implication in compulsive eating disorders, our findings suggest a role of an active reward system during sleep in the manifestation of SRED.